(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
With the introduction of computers into the educational process, there has been a gradual modernization of methods and techniques used in the classroom. Internet resources greatly facilitate the work of teachers in lesson planning and delivery. School teachers often use educational games, websites with interactive exercises, test assignments, as well as culturally informative videos that always spark genuine interest among students. The share of the English-language sector on the Internet has significantly exceeded others since the inception of the World Wide Web. Internet resources are actively being integrated into the education system, including the process of teaching foreign languages to students.